Cobrotoxin from Naja naja atra Venom Ameliorates Adriamycin Nephropathy in Rats. (11th November 2015) - Wang, Shu-Zhi; Xu, Yin-li; Zhu, Qi; Kou, Jian-qun; Qin, Zheng-Hong
Abstract : Chronic kidney disease (CKD) becomes a global health problem with high morbidity and mortality. Adriamycin- (ADR-) induced rodent chronic nephropathy is a classic experimental model of human minimal lesion nephrotic syndrome. The present study investigated the effect of cobrotoxin (CTX) on ADR-induced nephropathy. Rats were given 6 mg/kg ADR once through the tail vein to replicate ADR nephropathy model. CTX was administered to rats daily by placing a fast dissolving CTX membrane strip under the tongue starting from 5 days prior to ADR administration until the end of experiment. The results showed that CTX ameliorated the symptoms of ADR nephropathy syndrome with reduced body weight loss, proteinuria, hypoalbuminemia, dyslipidemia, serum electrolyte imbalance, oxidative stress, renal function abnormities, and kidney pathological lesions. Anti-inflammatory cytokine IL-10 expression was elevated after CTX administration in ADR nephropathy model. CTX inhibited the phosphorylation of I κ B- α and NF- κ B p65 nuclear translocation. Meanwhile, CTX upregulated the protein level of podocyte-specific nephrin and downregulated the level of fibrosis-related TGF- β . These findings suggest that CTX may be a potential drug for chronic kidney diseases.